Weissenberg and williamson mhd flow over a stretching surface with thermal radiation and chemical reaction - Ali, Karmina K.; Varol, Asaf (Pushpa Publishing House, 2019)
This survey investigates the characteristic flow, heat transfer and chemical reaction of Weissenberg and Williamson over a stretching sheet with thermal radiation and viscous dissipation. The nonlinear differential equation of the thermal boundary layer, which covers the physical problem, is derived and used to transform its equations into a system of higher nonlinear ordinary differential equations with similarity. The resulting non-monthly equation system is numerically solved using the explicit Runge-Kutta technique with the shooting technique. The behavior of the favorite physical parameters with different values in the speed profile, heat transfer, concentration of nanoparticles, skin friction, Nusselt number and Sherwood number has been discussed and graphically analyzed. © 2019 Pushpa Publishing House, Prayagraj, India http://www.pphmj.com.
Keywords: Flow of boundary layers; Heat transfer; Thermal radiation; Williamson and Weissenberg fluids